Integrating geospatial technologies and AHP for optimal urban green space development: a case study of Gondar, Ethiopia - Bewketu Kiberet; Assayew Nebere; Bantayehu Ayalew Workineh; Muralitharan Jothimani (Discover Sustainability)
Abstract Urban green spaces are crucial for improving city dwellers' environmental, social, and health well-being. This study explores how geospatial technologies can be used to identify optimal areas for green space development in Gondar, Ethiopia. Applying the Analytic Hierarchy Process (AHP), the study assesses seven key factors: land use, road access, soil quality, proximity to water sources, population density, historical landmarks, and slope suitability. The data collection approach consisted of field observations, interviews, and existing document analysis; remote sensing data from Sentinel-2A images and Geographic Information System (GIS) technology enhancing this procedure. The land suitability analysis revealed 164.93 hectares as very appropriate, 3227.54 hectares as suitable, and 2949.7 hectares as quite ideal for the development of green space. The study indicates that, among other factors, the development of urban green zones depends mostly on accessibility to roads and streams, moderate slopes, and some land use types and other features. The findings highlight that accessibility to roads and water, moderate slopes, and specific land uses are critical for green space planning. This research offers valuable insights for urban planners and policymakers, providing strategies for sustainable urban development and enhancing the resilience of rapidly growing cities like Gondar. Additionally, it underscores the importance of integrating environmental and community needs in green space planning.